Sosialisasi Pemberdayaan Masyrakat Melalui Bimbingan Teknis Home Industry Pengelolaan Cengkeh Dan Pala Di Desa Takofi Kecamatan Moti - Bambang Tjiroso; Mukhlis Muslimin; Sandi Rais; Syamsul Bahri LM (Patria Artha Journal of Community (PKM), 2022)
The 2022 PKM activities carried out by the Mechanical Engineering Study Program, Faculty of Engineering, Khairun University, were completed in Takofi Village, Pulau Moti District. Takofi Village is one of the villages located in Pulau Moti District, with the average population working as farmers and fishermen. One of the biggest fertilizer producers from this village is cloves and nutmeg. The clove and nutmeg home processing industry in this village can be said to be very minimal. The clove and nutmeg marketing process carried out by the people of Takofi Village is usually carried out individually by the farmers and then sold to Village collectors; there are also itinerant traders who come from door to door to buy dried cloves from clove farmers who want to sell their cloves to them and some are sold directly to Ternate. The dedication results show that partners easily understand and practice the training material. This is evident from their ability to make several processed clove and nutmeg products, such as making clove oil and processed nutmeg products into candied nutmeg as taught. Through this activity, partners can be motivated to become entrepreneurs by utilizing existing local potential. Thus, the existing natural resources can not only be used optimally but also can generate added value for the family economy.Keywords:  Cloves, Nutmeg, Community Empowerment, Takofi Village.